Digitalitas Usaha Mikro: Transformasi Ekosistem Ekonomi Kreatif pada Street Food Halal di Kota Medan - Meliyani Meliyani; Arifa Pratami; Ismail Ismail (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to analyze the impact of the creative economy ecosystem through digital platforms on the empowerment of halal street food micro-enterprises in Medan. Using a descriptive qualitative method, data were collected through in-depth interviews with 5 informants who are micro-culinary entrepreneurs. The results show that digital platform integration provides a transformative impact in the form of massive market expansion to suburban areas without requiring physical expansion, as well as creating business resilience that maintains turnover stability against weather disruptions. Managerially, digital platforms serve as a source of financial management education; access to sales history allows entrepreneurs to predict demand fluctuations, effectively minimizing losses due to food waste and optimizing working capital. Finally, the digital ecosystem accelerates product standardization through value creation demands on visual aspects and quality, as well as driving the acceleration of halal certification as a primary instrument for building credibility and digital trust. These findings conclude that digital platforms are not merely sales channels, but an empowerment infrastructure that enhances professionalism and sustainability for micro-enterprises within the creative economy ecosystem.